Chemogenetic activation of locus coeruleus neurons ameliorates the severity of multiple sclerosis - Alejandro Torrillas-de la Cal; Sonia Torres-Sanchez; Lidia Bravo; Meritxell Llorca-Torralba; Jose Antonio Garcia-Partida; Ana I. Arroba; Esther Berrocoso (Journal of Neuroinflammation, 2023)
Abstract Background Most current disease-modifying therapies approved for multiple sclerosis (MS) are immunomodulatory drugs that counteract the aberrant activity of the immune system. Hence, new pharmacological interventions that drive anti-inflammatory activity and neuroprotection would represent interesting alternative therapeutic approaches or complementary strategies to treat progressive forms of MS. There is evidence of reduced noradrenaline levels and alterations to locus coeruleus (LC) noradrenergic neurons in MS patients, as well as in animal models of this disease, potentially factors contributing to the pathophysiology. Drugs that enhance noradrenaline appear to have some beneficial effects in MS, suggesting their potential to dampen the underlying pathology and disease progression. Methods Therefore, we explored the consequences of chronic LC noradrenergic neurons activation by chemogenetics in experimental autoimmune encephalomyelitis (EAE) mice, the most widely used experimental model of MS. LC activation from the onset or the peak of motor symptoms was explored as two different therapeutic approaches, assessing the motor and non-motor behavioral changes as EAE progresses, and studying demyelination, inflammation and glial activation in the spinal cord and cerebral cortex during the chronic phase of EAE. Results LC activation from the onset of motor symptoms markedly alleviated the motor deficits in EAE mice, as well as their anxiety-like behavior and sickness, in conjunction with reduced demyelination and perivascular infiltration in the spinal cord and glial activation in the spinal cord and prefrontal cortex (PFC). When animals exhibited severe paralysis, LC activation produced a modest alleviation of EAE motor symptoms and it enhanced animal well-being, in association with an improvement of the EAE pathology at the spinal cord and PFC level. Interestingly, the reduced dopamine beta-hydroxylase expression associated with EAE in the spinal cord and PFC was reversed through chemogenetic LC activation. Conclusion Therefore, clear anti-inflammatory and neuroprotective effects were produced by the selective activation of LC noradrenergic neurons in EAE mice, having greater benefits when LC activation commenced earlier. Overall, these data suggest noradrenergic LC neurons may be targets to potentially alleviate some of the motor and non-motor symptoms in MS.